Immunological aspects of endometriosis: a review - Králíčková, Milena; Vetvicka, Vaclav (Annals of translational medicine, 2015)
Endometriosis is a common and serious illness affecting women in their reproductive years. Despite the ongoing interest and intensive research of this crippling disease, the cause remains unknown since its first description over 150 years ago. The origins and genesis of endometriosis, despite numerous hypotheses, are still unclear. One of the possible causes of the development of endometriosis might be the immune system, despite the fact that endometriosis is generally considered to be a steroid-sensitive disease. Numerous aspects of the immune system has been found changed, from the different number of activated macrophages to different subtypes of lymphocytes and their activities, suggesting involvement of immunity. On the other hand, it is possible that immunological changes around the endometriotic lesion are only secondary to the establishment of endometriosis. In this review, we will summarize the current knowledge of immunological reactions in endometriosis.
Keywords: immunology; Endometriosis; lymphocytes; cytokines